A New Seleukid Mint: Samarkand – Marakanda - Gorin, Aleksei N. (Anabasis. Studia Classica et Orientalia, 2015)
The paper considers a group of four unique copper coins. These coins, representing a new type: crab / bee with the legend ‘King Antiochos’, were found between 2004 and 2012 at the site of Afrasiab – the ancient capital of Sogdiana (Marakanda) – and nearby. In the first publication of these coins, A. Atakhodzhaev attributed the coinage to the Seleukid king Antiochos III (223–187 B.C.) during his eastern campaign (c. 212–204 B.C.). The author argues that this coinage should instead be assigned to Antiochos I (ca. 295–281 B.C. – as co-ruler of the eastern satrapies, 281–261 B.C. – as sole ruler) or Antiochos II (261–246 B.C.). It is further postulated that the short-lived mint of Marakanda operated between c. 280 and 250 B.C.